Near‐bed and surface flow division patterns in experimental river bifurcations. Issue 2 (22nd February 2014) - Marra, Wouter A.; Parsons, Daniel R.; Kleinhans, Maarten G.; Keevil, Gareth M.; Thomas, Robert E.
Abstract: Understanding channel bifurcation mechanics is of great importance for predicting and managing multichannel river processes and avulsion in distributary river deltas. To date, research on river channel bifurcations has focused on factors determining the stability and evolution of bifurcations. It has recently been shown that, theoretically, the nonlinearity of the relation between sediment transport and flow discharge causes one of the two distributaries of a (slightly) asymmetrical bifurcation to grow and the other to shrink. The positive feedback introduced by this effect results in highly asymmetrical bifurcations. However, there is a lack of detailed insight into flow dynamics within river bifurcations, the consequent effect on bed load flux through bifurcating channels, and thus the impact on bifurcation stability over time. In this paper, three key parameters (discharge ratio, width‐to‐depth ratio, and bed roughness) were varied in order to examine the secondary flow field and its effect on flow partitioning, particularly near‐bed and surface flow, at an experimental bifurcation. Discharge ratio was controlled by varying downstream water levels. Flow fields were quantified using both particle image velocimetry and ultrasonic Doppler velocity profiling. Results show that a bifurcation induces secondary flow cells upstream of the bifurcation. In the case of unequal discharge ratio, a strong increase in the secondary flow near the bed causes a larger volume of near‐bed flow to enter the dominant channel compared to surface and depth‐averaged flow. However, this effect diminishes with larger width‐to‐depth ratio and with increased bed roughness. The flow structure and division pattern will likely have a stabilizing effect on river channel bifurcations. The magnitude of this effect in relation to previously identified destabilizing effects is addressed by proposing an adjustment to a widely used empirical bed load nodal‐point partition equation. Our finding implies that river bifurcations can be stable under a wider range of conditions than previously thought. Key Points: Secondary flow in symmetrical bifurcations causes strong near‐bed flow curvature A disproportional amount of near‐bed flow enters the dominant downstream channel Flow curvature adds a stabilizing feedback on bifurcation evolution